Peran Orang Tua Dalam Pembinaan Sepak Bola Usia Dini di SSB Bina Putra Pamekar - Buchori, Anggi Al; Sudirjo, Encep; Saptani, Entan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to examine the role of parents in developing early childhood football at SSB Bina Putra Pamekar, Sumedang Regency. The research method used is qualitative, with data collection techniques through observation, interviews, and documentation study. The research results show that the role of parents in early childhood football development at SSB Bina Putra Pamekar can be categorized into three: motivators, facilitators, and supporters. The role of parents as motivators is evident in providing encouragement, enthusiasm, and motivation to their children to continue training and achieving success. The role of parents as facilitators is apparent in providing the facilities and infrastructure needed for children to practice, such as soccer shoes, jerseys, and other training equipment. The role of parents as supporters is evident in providing encouragement and motivation to their children during matches, both directly on the field and indirectly through prayers and moral support. In conclusion, parents' role in early childhood football development at SSB Bina Putra Pamekar can be categorized into three: motivators, facilitators, and supporters Keywords: Bina Putra Pamekar Football Academy, Grassroots football development, parental roles,